High prevalence of enteroviral genomic sequences in myocardium from cases of endemic cardiomyopathy (Keshan disease) in China. Issue 6 (1st June 2000) - Li, Y; Peng, T; Yang, Y; Niu, C; Archard, L C; Zhang, H
Abstract : OBJECTIVE: To verify the aetiological involvement of enterovirus and identify the viral genomic sequences in Keshan disease. DESIGN: Formalin fixed, paraffin embedded myocardial necropsy tissue samples were collected in Keshan disease endemic regions. Fourteen cases with a histologically confirmed diagnosis of subacute or chronic Keshan disease were studied. Control tissue included 10 samples of myocardium from cases of cerebral trauma and one from accidental acid intoxication. One sample from a case of enteroviral myocarditis was used as a positive control. The presence of viral genomic RNA was investigated using an established reverse transcription nested polymerase chain reaction (PCR) coupled with direct nucleotide sequencing. Further investigations of PCR positive samples included in situ antigen detection or hybridisation to confirm positive results. RESULTS: Nine of 14 myocardial samples from Keshan disease cases and the positive control were positive for the enteroviral RNA. All the controls were negative. Six of the PCR positive samples were investigated further by in situ enteroviral antigen or RNA detection and all were positive. DNA sequencing of six representative PCR products confirmed that they were homologous to the 5' non-translated region of enteroviral genomic RNA. Five had highest homology to coxsackievirus B genotypes and one was identical to poliovirus type 3. CONCLUSIONS: These results support an aetiological role for enteroviral infection in Keshan disease. Nucleotide sequence data suggest that coxsackievirus B or coxsackie B like viruses are often involved in Keshan disease.